Development and Validation of a Centralised Procurement Model: The Key Role and Intermediary Role in Strengthening Procurement Governance (Case Study of PT Wika Gedung) - Yayuk Dwi Indriani; Agus Purnomo; Melia Eka Lestiani (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to develop and validate a centralised procurement model in the construction industry using Exploratory Factor Analysis (EFA) and Partial Least Squares Structural Equation Modelling (PLS-SEM). The EFA results identified six new factors representing the multidimensional nature of centralised procurement: ORCHESTRA, STRATEGUS, DIGISONIC, FINCERTO, SYMPHONY-LINK, and GRAND-GOVERNANCE. All constructs showed strong statistical validity and reliability. The PLS-SEM findings showed high explanatory power, with R² values of 0.732 for SYMPHONY-LINK and 0.731 for GRAND-GOVERNANCE. These results highlight that STRATEGUS significantly influences SYMPHONY-LINK, while SYMPHONY-LINK is the dominant predictor in procurement governance. Furthermore, SYMPHONY-LINK fully mediates the effect of STRATEGUS on GRAND-GOVERNANCE, highlighting cross-functional integration as a critical driver of centralised procurement success. This study contributes theoretically by introducing new constructs into the domain of centralised procurement and provides practical implications for construction companies seeking standardised, transparent, and sustainability-oriented procurement strategies.